Loss of Folliculin disrupts hematopoietic stem cell quiescence and homeostasis resulting in bone marrow failure - Baba, Masaya (Stem Cells, 2016)
Folliculin (FLCN) is an autosomal dominant tumor suppressor gene that modulates diverse signaling pathways required for growth, proliferation, metabolism, survival, motility and adhesion. FLCN is an essential protein required for murine embryonic development, embryonic stem cell (ESC) commitment, and Drosophila germline stem cell maintenance, suggesting that Flcn may be required for adult stem cell homeostasis. Conditional inactivation of Flcn in adult hematopoietic stem/progenitor cells (HSPCs) drives HSC into proliferative exhaustion resulting in the rapid depletion of HSPC, loss of all hematopoietic cell lineages, acute bone marrow failure, and mortality after 40 days. HSC that lack Flcn fail to reconstitute the hematopoietic compartment in recipient mice, demonstrating a cell-autonomous requirement for Flcn in HSC maintenance. Bone marrow cells (BMC) showed increased phosphorylation of Akt and mTorc1, and extramedullary hematopoiesis was significantly reduced by treating mice with rapamycin in vivo, suggesting that the mTorc1 pathway was activated by loss of Flcn expression in hematopoietic cells in vivo. Tfe3 was activated and preferentially localized to the nucleus of Flcn knockout (KO) HSPCs. Tfe3 overexpression in HSPCs impaired long term hematopoietic reconstitution in vivo, recapitulating the Flcn KO phenotype, and supporting the notion that abnormal activation of Tfe3 contributes to the Flcn KO phenotype. Flcn KO mice develop an acute histiocytic hyperplasia in multiple organs, suggesting a novel function for Flcn in macrophage development. Thus, Flcn is intrinsically required to maintain adult HSC quiescence and homeostasis, and Flcn loss leads to bone marrow failure and mortality in mice.